Transurethral En bloc excision of pediatric bladder tumor using holmium laser - Pankaj N Maheshwari; Anant P Pore; Saurabh R Patil; Nick Okwi (Wolters Kluwer Medknow Publications, 2019)
A 12-year-old male child, during evaluation of chronic constipation, was incidentally diagnosed to have a fronded bladder growth. Transurethral en bloc excision of the tumor was achieved using holmium laser. Histopathology confirmed it to be an inflammatory pseudotumor. This case is reported for its unusual presentation and management by holmium laser.